2013
DOI: 10.1016/j.ultrasmedbio.2013.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Assessment of Elastic Modulus of Arterial Constructs during Cell Culture Using Ultrasound Elasticity Imaging

Abstract: Mechanical strength is a key design factor for engineered arteries. Most existing techniques assess the mechanical property of arterial constructs destructively, leading to a large number of animal sacrifices. We propose an ultrasound-based non-invasive mechanical strength assessment technique for engineered arterial constructs. Tubular scaffolds made from a biodegradable elastomer and seeded with vascular fibroblasts and smooth muscle cells were cultured in a pulsatile-flow bioreactor. Scaffold distension was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…These data revealed good correspondence with the bi-axial tensile test. Other similar studies determined mainly the Young's modulus and found good agreement between inflation experiments and bi-axial tensile testing (Dutta et al 2013;Kim et al 2008). Although the Young's modulus is also a linear elastic parameter, it is valid only for small strains, whereas the neo-Hookean model can also be used to describe large deformations such as those found in this study.…”
Section: Neo-hookean Modelsupporting
confidence: 75%
“…These data revealed good correspondence with the bi-axial tensile test. Other similar studies determined mainly the Young's modulus and found good agreement between inflation experiments and bi-axial tensile testing (Dutta et al 2013;Kim et al 2008). Although the Young's modulus is also a linear elastic parameter, it is valid only for small strains, whereas the neo-Hookean model can also be used to describe large deformations such as those found in this study.…”
Section: Neo-hookean Modelsupporting
confidence: 75%
“…In all three cases, the partial-field measurements were assumed to be obtained from some type of nondestructive testing in the linear range of the solid behavior. First, two numerical examples were considered in which the "experiment" was simulated through finite element analysis, as described in Section 3.1, then a physical (i.e., "real life") example was considered relating to elastography of an arterial construct [33].…”
Section: Examples and Discussionmentioning
confidence: 99%
“…Successful translation of such technologies, especially with aids of Gappy POD for realistic computational power, can result in significant savings in time and money for both noninvasive preclinical studies and clinical uses. The example followed a nearly identical format as the work shown in [33], with the exception of the inverse solution estimation procedure (the prior work used a computationally expensive non-gradient-based optimization procedure). For simplicity, the behavior of the artery for all analyses was assumed to obey the plane strain condition, and the initial cross-sectional geometry of the artery was estimated from ultrasound imaging, as shown in Fig.…”
Section: Ultrasound Imaging Experiment: Elastography Of An Arterial Cmentioning
confidence: 99%
See 2 more Smart Citations